Major Drivers and Effects of Land degradation in Nigeria: A Review - Umoru, Kebiru (International Journal of Scientific Research in Biological Sciences, 2023)
Land degradation is the process of land destruction, which is usually prompted by both anthropogenic and natural activities. It is one of the major environmental problems especially in developing countries. The focus of this paper is to review the studies on the main drivers and effects of land degradation phenomenon in Nigeria. Some of the major causes are discussed including deforestation and forest degradation, overgrazing, bush burning, and mining. This study also indicate that land degradation has severe negative effects on the ecosystem some of which are desertification and drought, loss of agrarian land, low crop production, and soil erosion, etc. Furthermore, the approach to manage land degradation is presented, and it was pointed out that the advantage of using remotely sensed data in land degradation assessment is that it provides a cost-effective, timely, and consistent evidence of degraded lands regularly.